The Impact of Application of International reporting Standards on the Reporting of the Key Audit Matters - SAHIB, SAHAR Y.; HAMDAN, KHAWLA H. (The journal of contemporary issues in business and government, 2021)
This research examined how the implication international financial reporting standards (IFRS) are related to the main audit aspects in the report of the auditor. The application of these standards could help many essential matters appear. In the report of auditor, these matters are to be disclosed. However, the current Iraqi auditor report does not include any clarifications to users on how to deal with these matters as a result of not applying auditing standard No. (701) accordingly.